Evaluation of Budget Spending Sustainability of DKI Jakarta Provinceâ€™s Budget - Wirawan, Sri Mahendra Satria (Research and Development Agency Ministry of Home Affairs, 2018)
The budget spending in the Regional Governmentâ€™s Budget (APBD) is one of the indicators of the success of the regional development. DKI Jakarta Provinceâ€™s APBD spending is seen to be sub-optimal, with the average of 75.79% in the last 5 years (2012-2016), below the 95% target set out by the Minister of Finance. As such, a study is required to review why it happens and what factors need to be addressed to optimize the DKI Jakarta Provinceâ€™s APBD spending. The previous study conducted to analyze the low spending in the Ministries/Institutions and Regional Government in general. This study is conducted to understand the sustainability of the budget spending and to identify the types of spending that might be the driver to optimize the DKI Jakarta Provinceâ€™s APBD spending, enabling the province realized its development target and directly providing a desirable impact the public and the business world, increase their trust to the government and in turn will push the DKI Jakartaâ€™s economic growth. This study uses Multidimensional Scaling (MDS) with a secondary data from The Regional Government Financial Report (LKPD) of DKI Jakarta Province for the year of 2012 to 2016 and the End-of-Term Accountability Report (LKPJ-AMJ) of DKI Jakarta Province of the Year 2013 to 2017 (2016a). The result of this study shows that the average DKI Jakarta Provinceâ€™s APBD spending of the last five years (2012-2016) is 47.64 or fall under the category of â€œless sustainableâ€, whereas the spending items causing the unfavorable result are the social benefits, grants, land acquisitions and buildings and structures spending. As such, it is recommended that the DKI Jakarta Provincial Government establishes a more measurable policy on planning, budgeting and execution and to increase the competence of its apparatus.